School principal strategies in improving the competitiveness - Sri Kuryani; Yasir Arafat; Mulyadi Mulyadi (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aimed to determine and analyze knowing and describing the principal's strategy in increasing the competitiveness of SD Negeri 1 Supat, Babat Supat District. This type of research was descriptive qualitative research. Data collection tools used were documentation, interviews, observation and literature review. The data analysis technique used was descriptive qualitative analysis technique which consisted of data collection, data reduction, data presentation, and drawing conclusions and fermentation. The results of the study stated that 1) the principal's strategy in increasing competitiveness at SD Negeri 1 Supat, Babat Supat District a) planning a program to improve the quality and competitiveness of the school both in the short and long term; b) determine the program that has been planned in the form of an activity instrument which is carried out in SD Negeri 1 Supat, Babat Supat District; and c) implement the strategy set by the school; 2) The obstacles faced in efforts to increase competitiveness lie in efforts to improve the quality of learning at SD Negeri 1 Supat; and 3) Solutions to some of the obstacles faced in increasing competitiveness through the quality of learning at SD Negeri 1 Supat, among others by: a) implementing continuous coaching to increase the experience and knowledge of teachers; b) supervise teachers as well as evaluate and provide direction for improvement. Provide training and assignments to improve teacher skills; c) assignments in various activities both at school and outside of school and provide opportunities for teachers to interact and communicate with many parties; and d) capacity building activities carried out through sending training participants, workshops, socialization, training, and KKG activities.